2008
DOI: 10.1007/s00432-008-0377-3
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen for salivary gland adenoid cystic carcinoma: report of two cases

Abstract: Given the relatively unsuccessful treatments for ACC-SC and the low toxicity of ER antagonists, such therapy should be considered in these patients for its potential disease-stabilizing effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 12 publications
0
29
0
Order By: Relevance
“…It has been suggested that there may be a hormonal influence accounting for the different biological behaviors of ACC among the sexes. 22 Reports of αER and PR expression in salivary gland ACC range from 0% to 100%. 23-25 Possible explanations for this variation include clone variability and different methods of antigen retrieval.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that there may be a hormonal influence accounting for the different biological behaviors of ACC among the sexes. 22 Reports of αER and PR expression in salivary gland ACC range from 0% to 100%. 23-25 Possible explanations for this variation include clone variability and different methods of antigen retrieval.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it has been reported that some SGC possess hormonal receptors, such as estrogen [88] or progesterone [89-92] or even androgen receptors in salivary duct carcinoma [92]. In light of these reports, hormonal treatment has been used occasionally, and isolated case reports document objective responses in patients with ACC treated with tamoxifen [93,94] and in patients with salivary duct cancer and adenocarcinoma treated with antiandrogen therapy [95,96]. To date, no phase II studies have been performed, so it is difficult to define the role of hormone therapy in SGC.…”
Section: Methodsmentioning
confidence: 99%
“…There are few reports on antihormone therapies in salivary gland carcinomas, although Elkin and Jacobs. 26 reported long-term therapeutic effect in two ACC patients treated with tamoxifen/toremifene. Thus, ER is another possibility for specific targeting in the treatment of patients with ACC.…”
Section: Discussionmentioning
confidence: 99%